A Joint Elliott Type Theorem for Twists of L-Functions of Elliptic Curves. Issue 6 (1st November 2016) - Garbaliauskienė, Virginija; Laurinčikas, Antanas
Abstract: We consider a collection of L -functions of elliptic curves twisted by a Dirichlet character modulo q ( q is a prime number), and prove for this collection a joint limit theorem for weakly convergent probability measures in the space of analytic functions as q → ∞. The limit measure is given explicitly.